SUMOylation of Arginyl tRNA Synthetase Modulates the Drosophila Innate Immune Response - Nayak, Prajna; Kejriwal, Aarti; Ratnaparkhi, Girish S. (Frontiers in Cell and Developmental Biology, 2021)
SUMO conjugation of a substrate protein can modify its activity, localization, interaction or function. A large number of SUMO targets in cells have been identified by Proteomics, but biological roles for SUMO conjugation for most targets remain elusive. The multi-acyl tRNA synthetase complex (MARS) is a sensor and regulator of immune signaling. The proteins of this 1.2 MDa complex are targets of SUMO conjugation, in response to infection. Arginyl tRNA Synthetase (RRS), a member of the sub-complex II of MARS, is one such SUMO conjugation target. The sites for SUMO conjugation are Lys 147 & 383. Replacement of these residues by Arg (RRSK147R,K383R), creates a SUMO conjugation resistant variant (RRS-SCR). Transgenic Drosophila lines for RRS-WT and RRS-SCR were generated by expressing these variants in a RRS null (ΔRRS) animal, using the UAS-Gal4 system. The ΔRRS line was itself generated using CRISPR/Cas9 genome editing. Both RRSWT and RRSSCR rescue the ΔRRS lethality. Adult animals expressing RRSWT and RRSSCR are compared and contrasted for their response to bacterial infection by gram positive M. luteus and gram negative Ecc15. We find that RRS-SCR, when compared to RRSWT, shows modulation of the transcriptional response, as measured by quantitative 3’ mRNA sequencing. Our study uncovers a possible non-canonical role for SUMOylation of RRS, a member of the MARS complex, in host-defense.